Microstructured optical fibers for sensing applications - Yong, Derrick Zhi Yong. (2011)
Fiber optics has been widely explored for its sensing applications on top of its use in telecommunications. Its numerous advantages over traditional sensors have progressively seen to its acceptance. With the device of microstructured optical fibers (MOFs), which possess manipulable optical properties, sensing capabilities have largely been enhanced in terms of precision and accuracy with their additional demonstration as feasible biosensors. Further to understanding the basics of optical fibers and novelty of MOFs, particularly light guidance within its microstructured array, sensing via three different MOF-based devices was studied. Notably, spectral information, quantified as wavelength, was analyzed with respect to measurand changes through experimentation and theoretical substantiation. The first device, a MOF integrated microfluidic chip, was utilized in real-time chemical sensing. Here, microfluidic manipulation and optical alignment was facilitated by the microfluidic chip. Through the analysis of output spectrum dips, an inherent property of MOFs due to bending induced oscillatory losses, a red-shifting phenomenon was observed with increasing refractive index of infiltrant.